2018
DOI: 10.1186/s12863-018-0600-4
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome scan reveals significant non-additive effects for sire conception rate in Holstein cattle

Abstract: BackgroundService sire has a considerable impact on reproductive success in dairy cattle. Most gene mapping studies for bull fertility have focused on additive effects, while non-additive effects have been largely ignored. The main goal of this study was to assess the relevance of non-additive effects on Sire Conception Rate (SCR) in Holstein dairy cattle. The analysis included 7.5 k Holstein bulls with both SCR records and 57.8 k single nucleotide polymorphism (SNP) markers spanning the entire genome.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…; Nicolini et al . ). This knowledge, however, cannot be transferred directly to Jerseys because this breed may exhibit differences in the pool of causative mutations, the extent of linkage disequilibrium, the phase between markers and causative mutations and the effects of the causative mutations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Nicolini et al . ). This knowledge, however, cannot be transferred directly to Jerseys because this breed may exhibit differences in the pool of causative mutations, the extent of linkage disequilibrium, the phase between markers and causative mutations and the effects of the causative mutations.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, our recent study revealed significant dominance effects for SCR on Holsteins (Nicolini et al . ). Here, using an efficient two‐step mixed‐model‐based approach, we identified two genomic regions on BTA11 (2.6 Mb) and BTA25 (19.2 Mb) with significant recessive effects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In fact, the relatedness encoded as spatial genetic distance between individuals is expected to capture some of the complexity of the genome, including nonadditive effects . It should be noted that Nicolini et al (2018) and Rezende et al (2018) have identified significant nonadditive effects underlying SCR in both Holstein and Jersey breeds. The better performance achieved by the Gaussian kernel can be due to its ability to capture the heterogeneous nature of this multi-breed reference population, including nonoverlapping major additive effects and important nonlinear effects.…”
Section: Incorporation Of Holstein Records In the Reference Populationmentioning
confidence: 99%
“…On the other hand, and despite its importance, the genetic improvement of dairy bull fertility has received less attention. Our group has recently identified candidate genomic regions, individual genes, and biological processes underlying bull fertility in Holstein cattle (Han and Peñagaricano, 2016;Nicolini et al, 2018), as well as reported promising results for predicting Holstein SCR values using genomic data (Abdollahi-Arpanahi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%